PEMBERIAN STIMULAN ETEFON DENGAN TEKNIK GROOVE APPLICATION PADA PRODUKSI LATEKS TANAMAN KARET (Hevea brasiliensis Muell Arg.) - Khairil Fahmi; Sampoerno '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this study was to know the effect of giving stimulant ethephon to latex production increase and to obtain the best dose of stimulant ethephon with groove application technique. The experiment was carried out rubber plantation of  citizenry. Bencah Kelubi village, Tapung Subdistrict, Kampar Regency from February to March 2015.The study arranged experimentally using Completely Randomized Block Design with five treatments and Four block then obtained 20 experimental units. The treatments were ethephon dose 0 cc plant-1 (without ethephon’s application), ethephon dose 0,3 cc plant-1, ethephon dose 0,6 cc plant-1, ethephon dose 0,9 cc plant-1, and ethephon dose 1,2 cc plant-1. Parameters observed were duration of latex flow, volume of latex and Dry Rubber Content. Data were analyzed statistically using ANOVA and followed by LSD at level of 5%. The results showed that ethephon’s application real effect to increase on duration of latex flow and the volume of latex. ethephon’s application dose 0,3 cc plant-1 showed the best result for duration of latex flow (the increase of 0 cc plant-1 were 0,321 ml/minute) and volume of latex (the increase of control were 25,633 ml. Ethephon’s application dose 0,3 cc plant-1 showed dry rubber content relatively better than other treatment were 71,078%. Keywords : Heveabrasiliensis Muell Arg., ethephon, groove application